asy-Syi’ru “Man ‘Allamani Hubban Kuntu lahu ‘Abdan” li Nizar Qabbani (at-Tahlil as- Simiyai li Michael Riffaterre) - Abdul Latif; Nur Safitri (Postgraduate of IAIN Metro Lampung Indonesia, 2019)
The poetry was